Comparing the sensitivity of the box task combined with the detection response task to the lane change test. (February 2023) - Morgenstern, Tina; Trommler, Daniel; Naujoks, Frederik; Karl, Ines; Krems, Josef F.; Keinath, Andreas
Highlights: The sensitivity of the Box Task (BT) combined with a tactile Detection Response Task (DRT) was compared to the Lane Change Test (LCT). BT is sensitive to visual-manual secondary task demand. DRT is sensitive to cognitive secondary task demand. The standard LCT parameter was not as effective in discriminating between secondary tasks. Combining the BT with a tactile DRT provides a more accurate distinction between different task types and difficulty levels than the standard version of the LCT. Abstract: The Box Task combined with a Detection Response Task (BT + DRT) is a relatively new and easy-to-use method to assess in-vehicle system demand, consisting of a visual-manual task (BT) and a cognitive task (tactile DRT). Currently, little is known regarding the sensitivity of the BT + DRT for different types and difficulty levels of secondary tasks. Therefore, the present study evaluated the BT + DRT's sensitivity compared to the Lane Change Test (LCT), which is an ISO-standardized test method. Fifty-two participants engaged in a visual-manual (Surrogate Reference Task) and a cognitive secondary task (counting task) across two levels of difficulty while performing a PC version of the BT + DRT and LCT. The BT parameters, especially the standard deviation of box position and size, were sensitive to visual-manual secondary task demand. Moreover, the results showed that the DRT is a sensitive method to assess cognitive demand, supporting previous findings. In contrast, the mean deviation of the adaptive reference lane used as the standard LCT parameter was not as effective in discriminating between visual-manual and cognitive tasks. Hence, to distinguish between different types and levels of secondary task demand, the BT + DRT is more accurate than the standard LCT version. Future studies should investigate how an increased BT difficulty can further improve the sensitivity to visual-manual and cognitive secondary task demand.